Basque Boys Training Committee (statement) (1939)
1939 038-0082-003 BASQUE CHILDREN'S COMMITTEE CHAIRMAN: THE DUCHESS OF ATHOLL, D.B.E., D.C.L. VICE-CHAIRMEN: MISS ELEANOR RATHBONE, M.P. H.V. TEWSON, ESQ. HON. SECRETARIES: Mr. WILFRID ROBERTS, M.P. LT.-COL. J.R.J. MACNAMARA, M.P. Mr. D.R. GRENFELL, M.P. HON. TREASURER: VISCOUNT CECIL OF CHELWOOD, P.C. K.C. ORGANISING SECRETARY: DR. BETTY MORGAN. 30, ECCLESTON STREET, [4, GREAT SMITH STREET,] LONDON, S.W.1. TELEPHONE: [ABBEY 2565] SLOANE 9866 BASQUE BOYS TRAINING COMMITTEE. The Basque Boys Training Committee was formed to take over the responsibility for all the older Basque boys in England who may never be able to return to Spain. There are some one hundred and fifty boys between the ages of fourteen and eighteen, whose parents are dead or missing, in prison or in the concentration camps, or being subjected to political victimisation. For each of these boys, with the co-operation of the Trade Union Movement, we aim to provide a training in agriculture or industry that will enable him eventually to support himself, whether he emigrates or whether he becomes a naturalised British subject. We have Home Office permission for the boys to be placed in work, provided in every case that the following conditions are observed:- (1). The proposed employment of a foreigner must be reasonable in the circumstances. (2). The wages and other conditions of employment proposed for a foreigner must not be less favourable than those commonly accorded to British employees in the trade in the district concerned. (3). The employment of a foreigner must not prejudice the position affecting employment of any British subject. Under these conditions, and with the help of Trade Union Committees and sympathetic persons and organisations, work has already been found for a number of boys in offices and hospital laboratories, machine-shops and garages, a building contractors, a cabinet-factory, with electrical engineers and on farms. But we still have a hundred or more to place, and the problem is urgent. Their life tomorrow depends on today's help. Please help us to make it a good life. 292/946/38/82(III)